Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Nguyễn Phước Lộc (Số: 11497/BCT-KH) - Bộ Công thương (2016)
Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Nguyễn Phước Lộc (Số: 11497/BCT-KH) ngày 30/11/2016